Implementation of project crashing among contractors in Pahang - Nur Farah Najwa, Mat Lazin (2015)
This study seeks to identify the implementation of project crashing among contractors in Pahang. Project crashing is to shorten the actual project duration. The process that needs to accelerate the construction projects completion is called schedule compression. Project crashing is also to reduce the completion time of a project by sharply increasing manpower or other expenses. The objectives of this study are (1) to identify the factors that drive the organization to implement project crashing in construction project and (2) to study the challenges faced by the organization during the implementation of project crashing. There are two types of data collections used which are primary data and secondary data. For this research, the secondary data are from journals, books, articles and websites. The primary data is questionnaire survey that is considered as quantitative data. The questionnaire had been distributed to the respondents which are G7 class Construction Company in Pahang. The questionnaires are distributed to 100 companies and the data obtained are 72 respondents. From the findings, the most gender that becomes the respondents is female. The results shows that most of the respondents agree that adverse weather become the factor to implement the project crashing. From the results, the most significant challenges faced by organization also are exposed. The most significant challenge is require additional work hours in crashing the project. It is conclude that project crashing is important method to complete the project early from the actual schedule. As a recommendation, the future researcher can expand the scope of study from one class of contractors to two class of contractors.